Novel role of the LPS core glycosyltransferase WapH for cold adaptation in the Antarctic bacterium Pseudomonas extremaustralis - Benforte, Florencia Carla; Colonnella, Maria Antonela; Ricardi, Martiniano María; Solar Venero, Esmeralda Clara; Lizarraga, Leonardo; López, Nancy Irene; Tribelli, Paula Maria (PLOS ONE)
Psychrotroph microorganisms have developed cellular mechanisms to cope with cold stress. Cell envelopes are key components for bacterial survival. Outer membrane is a constituent of Gram negative bacterial envelopes, consisting of several components, such as lipopolysaccharides (LPS). In this work we investigated the relevance of envelope characteristics for cold adaptation in the Antarctic bacterium Pseudomonas extremaustralis by analyzing a mini Tn5 wapH mutant strain, encoding a core LPS glycosyltransferase. Our results showed that wapH strain is impaired to grow under low temperature but not for cold survival. The mutation in wapH, provoked a strong aggregative phenotype and modifications of envelope nanomechanical properties such as lower flexibility and higher turgor pressure, cell permeability and surface area to volume ratio (S/V). Changes in these characteristics were also observed in the wild type strain grown at different temperatures, showing higher cell flexibility but lower turgor pressure under cold conditions. Cold shock experiments indicated that an acclimation period in the wild type is necessary for cell flexibility and S/V ratio adjustments. Alteration in cell-cell interaction capabilities was observed in wapH strain. Mixed cells of wild type and wapH strains, as well as those of the wild type strain grown at different temperatures, showed a mosaic pattern of aggregation. These results indicate that wapH mutation provoked marked envelope alterations showing that LPS core conservation appears as a novel essential feature for active growth under cold conditions. Fil: Benforte, Florencia Carla. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Biológica; Argentina Fil: Colonnella, Maria Antonela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Centro de Investigaciones en Bionanociencias "Elizabeth Jares Erijman"; Argentina Fil: Ricardi, Martiniano María. Consejo Nacional de ...